Research on Surface Metallization of Polyimide Film. Issue 1 (1st August 2022) - Wang, Nan; Zhao, Lianjing; Bai, Jingying; Xu, Junjie; He, Yanlong; Dong, Junwei; Zhang, Ligong
Abstract: In order to make the Polyimide (PI) film material have good surface conductivity and meet its application in aerospace fields, for example, radar antenna, in this paper, the highly chemically inert PI material on the surface was modified by alkaline etching, and the metal layer on the surface of PI film was then deposited by electroless copper plating technology, to give PI good surface conductivity and meet its application in aerospace fields, for example, radar antenna. The microstructure and properties of surface metal layer of PI film before and after surface modification were characterized by SEM, contact angle tester and resistance tester. After alkaline etching at room temperature, there is a staggered and evenly distributed protrusion structure with dendritic and rivet structures on the surface of PI. However, the PI film surface etched at 60 °C presents pits with different sizes and depths of etching holes, and the hydrophilicity of the PI film surface is enhanced after etching. The coating on the PI is uniform and dense, and has good conductivity. This research realizes the preparation of high conductivity and high bonding force metal layer on the surface of PI film under alkaline etching, which provides technical support for the application of polyimide in aerospace fields.